Effects of pre-harvest application of 1-methylcyclopropene (1-MCP) on the postharvest quality of 'Cavendish' banana (Musa cavendishii) - Matuginas, John Paul L.; Manigo, Bryl I. (2020)
Several researches have been conducted to investigate the effect of 1-MCP in bananas, but inconsistencies in the results have been reported. Additionally, the effectiveness of 1-MCP is governed by various factors, such as cultivar, fruit maturity, concentration, time of exposure, and method of application. In this study, the effect of pre-harvest methods - Stalk End Immersion (SEI), bunch spraying (BS), Combination (SEI-BS), and Control - of 1-MCP application was determined by observing the postharvest quality of 'Cavendish' banana, such as peel yellowing, sensory firmness, visual quality, weight loss, degree of shriveling, fruit finger drop, organoleptic attributes, chemical properties, and disease incidence. Results revealed that pre-harvest 1-MCP (aqueous solution dosage of 400 nL/L) application through SEI and SEI-BS methods significantly retarded the peel color change up to 7 days of storage and prolonged the banana's shelf life for up to 19 days under ambient storage conditions. SEI-BS delayed fruit softening (for 15 days) and maintained visual quality (for 19 days) compared to SEI. Fruits treated with 1-MCP through SEI-BS had lesser accumulated weight loss, lower degree of shriveling, and reduced finger drop incidence compared to BS ad SEI methods conducted separately. In terms of cost efficiency, BS had lower cost compared to SEI and SEI-BS methods, while the chemical properties, organoleptic attributes, and disease incidence (crown discoloration, crown rot/mold, and banana anthracnose) failed to show any significant difference among pre-harvest methods.
Keywords: Mindanao studies; Cavendish banana